2018
DOI: 10.1177/0260106018772170
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with polyunsaturated fatty acids (PUFAs) in the management of attention deficit hyperactivity disorder (ADHD)

Abstract: While pharmacotherapy and psychosocial interventions are recommended as the primary frontline treatment for attention deficit hyperactivity disorder (ADHD), alternative approaches to managing ADHD are becoming increasingly popular among patients and their families. Supplementation with polyunsaturated fatty acids (PUFAs) is an example of this. PUFA supplementation is not recommended by guidelines for managing ADHD; however, patients may still decide to use it. To provide direction to healthcare professionals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
2
7
0
1
Order By: Relevance
“…Our findings displaying an inadequate effect of PUFA in the treatment of ADHD is in line with many previous reviews on the subject [ 57 , 61 , 62 , 63 , 64 , 65 ], but not all [ 66 , 67 , 68 , 69 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings displaying an inadequate effect of PUFA in the treatment of ADHD is in line with many previous reviews on the subject [ 57 , 61 , 62 , 63 , 64 , 65 ], but not all [ 66 , 67 , 68 , 69 ].…”
Section: Discussionsupporting
confidence: 93%
“…In conclusion, our study shows some benefits of EPA monotherapy on cognitive symptoms of ADHD. As amply discussed, it is possible that a combined EPA + DHA strategy might have been more beneficial, and as such we support the recent recommendation by a panel of ADHD experts that patients who prefer omega-3 supplements over stimulants should take a combination of DHA and EPA at doses ≥750 mg per day for at least 12 weeks 50 . However, we additionally recommend that this strategy should be even more strongly advocated for children with evidence of low endogenous PUFAs levels, as indicated by direct measurement, dietary habits or symptoms of EFA deficiency.…”
Section: Discussionsupporting
confidence: 80%
“…In a recent report of the "Omega Supplements in ADHD" Education Board meeting, eight international experts in the field of adult and child ADHD concluded that PUFA supplementation, in particular omega-3 PUFAs, may produce small but statistically significant reductions in ADHD symptoms while having a tolerable safety. 28 It should be noted that among the experts were few who already published evidence that PUFAs may improve behavior in ADHD. The experts noted that "the variation in results from the meta-analyses conducted, however, highlights the need for caution when interpreting studies."…”
Section: Pufas Supplementation For Adhdmentioning
confidence: 99%